Perhitungan Sebagai Seorang Investor Saham Atas Besaran Pajak Yang Harus Dibayarkan Kepada Negara - Ni Luh Dwik Suryacahyani Gunadi; Jose Widyatama (Jurnal Locus Delicti, 2021)
Investing is an activity that cannot be underestimated. Smart investing requires controlled analysis and management and investing is not a game. This study aims to provide a more in- depth description of the form of paper asset investment, namely stocks. Contains material from the most basic, namely what is shares to the calculation of taxes that must be paid by an investor or stock trader to the state for each transaction based on applicable provisions, namely Government Regulation Number 14 of 1997 concerning Amendments to Government Regulation Number 41 of 1994 concerning Income on Income From the Transaction of the Sale of Shares on the Stock Exchange